Four-Level Neutral Point Clamped Inverter Fed by 18-Pulse Diode Rectifier With Low Input and Output Harmonic Distortion: VERSION OF RECORD ONLINE: 17/09/2025 - Pham, Le Nam; Phan, Quoc Dung; Nguyen, Van Nho (Journal of Technical Education Science, 2025)
The four-level neutral point clamped (4L-NPC) inverter is a common and cost-effective topology among four-level inverters. However, balanced DC voltage sources at the input are necessary to ensure output quality. Therefore, this paper introduces a simplified power conversion system that includes an 18-pulse diode rectifier designed to supply the 4L-NPC inverter while significantly reducing harmonic distortion on both the input and output sides. The system employs an 18-pulse rectifier configuration to lower the harmonic content at the input and ensure a balanced DC voltage for the 4L-NPC inverter, thereby improving the quality of the output waveform. The combined system effectively reduces harmonic distortion on both the input and output sides, enhancing overall performance for industrial applications. Simulation results validate the system's ability to reduce Total Harmonic Distortion (THD) on the input while maintaining superior output performance from the 4L-NPC inverter. This approach provides an effective solution for high-power applications where controlling harmonic distortion is essential to meet strict power quality standards.